2019
DOI: 10.3233/jad-190181
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Meta-Analyses that Evaluate Risk Factors for Dementia to Evaluate the Quantity, Quality, and Global Representativeness of Evidence

Abstract: Background: The translation of evidence on dementia risk factors into clinical advice requires careful evaluation of the methodology and scope of data from which risk estimates are obtained. Objective: To evaluate the quantity, quality, and representativeness of evidence, we conducted a review of reviews of risk factors for Alzheimer’s disease (AD), Vascular dementia (VaD), and Any Dementia. Methods: PubMed, Cochrane library, and the Global I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
148
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(157 citation statements)
references
References 81 publications
(53 reference statements)
5
148
1
3
Order By: Relevance
“…A 2019 meta-analysis reviewed 91 articles involving 36 risk factors for AD [45]. The authors concluded that significant associations with AD decreased risk were found for alcohol consumption (any or light/moderate versus abstinence) from risk ratio (RR) = 0.43 (95% CI = 0.17-0.69) [46] to 0.72 (95% CI = 0.61-0.86) [47].…”
Section: Evidence From Epidemiological Studiesmentioning
confidence: 99%
“…A 2019 meta-analysis reviewed 91 articles involving 36 risk factors for AD [45]. The authors concluded that significant associations with AD decreased risk were found for alcohol consumption (any or light/moderate versus abstinence) from risk ratio (RR) = 0.43 (95% CI = 0.17-0.69) [46] to 0.72 (95% CI = 0.61-0.86) [47].…”
Section: Evidence From Epidemiological Studiesmentioning
confidence: 99%
“…Early work by committee members [13,14] and other recent reports such as the Lancet Commission [15] concluded that childhood education, exercise, maintaining social engagement, reducing smoking, and management of hearing loss, depression, diabetes, and obesity across the life course are key protective factors which collectively have potential to delay or prevent a third of dementia cases. The weight of evidence at present suggests that latelife cognitive decline and dementia are amenable to modification by treatment of vascular risk Evidence was collated from a number of large-scale reviews [17][18][19][20] and influenced by [13-16, 46, 47]. factors, increase in physical, mental, and social activity, and avoiding environmental hazards [16,17].…”
mentioning
confidence: 99%
“…Dazu zählen vor allem Hypertonie, körperliche Inaktivität, Fehlernährung, Übergewicht, Depression, Rauchen, Alkoholmissbrauch und Diabetes mellitus. Dieselben Risikofaktoren tragen nach gegenwärtiger Kenntnis auch zur Entstehung von Demenzen bei [7][8][9][10][11]. Ihre Elimination ließe nach einigen Modellrechnungen eine Reduktion der demenziellen Neuerkrankungen um etwa 30 % erwarten [12,13].…”
unclassified